A Convenient Approach to the Synthesis of Novel Substituted Cyclohexadienes by the Vinylogous Michael Addition of α,α-Dicyanoolefins - Alizadeh, Abdolali; Sedighian, Hadi; Bayat, Fahimeh (Synlett, 2014)
A concise and efficient approach to substituted cyclohexadienes has been developed. The method involves vinylogous addition of α,α-dicyanoolefins to Michael adduct intermediates, formed from malononitrile and dialkyl acetylenedicarboxylates, in the presence of triethylamine in ethanol. The method has the advantages of good yields and simple operations, and of not requiring a metal catalyst or an inert atmosphere.
Keywords: alkenes; nitriles; alkynes; Michael additions; cyclization; cyclohexadienes; addition